Why foreign ownership may be good for you - Hartmut Egger; Udo Kreickemeier (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
We develop a general equilibrium two-country model with heterogeneous producers and rent sharing at the firm level due to fairness preferences of workers. We identify two sources of a multinational wage premium. On the one hand, there is a pure composition effect because multinational firms are more productive, make higher profits, and therefore pay higher wages. On the other hand, there is a firm-level wage effect: A multinational firm pays higher wages in its home market than an otherwise identical national firm since it has higher global profits. We analyse how these two sources interact in determining the multinational wage premium in a setting with two identical countries, and show that in this case the wage premium is fully explained by firm characteristics. We then allow for technology differences between countries and find that a residual wage premium exists in the technologically backward country, but not in the advanced country.
urn:nbn:de:bsz:21-opus-58648
Keywords: D31; F12; F15; F16; H25; 330; multinational firms; wage premium; heterogeneous firms